1993
DOI: 10.2466/pms.1993.77.2.387
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Annihilation Anxiety from Projective Tests

Abstract: This report details procedures to measure annihilation anxiety, a concept derived from Freud's 1926 formulation of traumatic anxiety. A 25-item pencil-and-paper inventory administered to patient and to nonpatient samples is described, along with a brief summary of earlier findings. The delineation of nine interrelated experiential components of annihilation anxiety provides the background for the construction of Rorschach and TAT measures of the concept. Findings comparing the pencil-and-paper inventory and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 16 publications
3
26
2
Order By: Relevance
“…The Rorschach Content Scale (RCS) for annihilation anxiety. As noted above, the RCS for annihilation anxiety (Hurvich et al, 1993) operationalizes salient markers for annihilation anxiety found in the literature and clinical reports. The markers are fear of being overwhelmed, fear of merger, fear of disintegration, fear of impingement, fear of loss of needed support, inability to cope, fear of loss of self cohesion, concern over survival, and catastrophic mentality.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Rorschach Content Scale (RCS) for annihilation anxiety. As noted above, the RCS for annihilation anxiety (Hurvich et al, 1993) operationalizes salient markers for annihilation anxiety found in the literature and clinical reports. The markers are fear of being overwhelmed, fear of merger, fear of disintegration, fear of impingement, fear of loss of needed support, inability to cope, fear of loss of self cohesion, concern over survival, and catastrophic mentality.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Hurvich (Hurvich, Benveniste, Howard, & Coonerty, 1993) culled from the literature and from clinical and research reports what appear to be the most salient experiential correlates of annihilation anxiety.…”
Section: Appearance In the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Hurvich Experience Inventory (HEI), and its different versions (Allen, Hurvich, & Mcguire, 2017) is a self-report protocol that associate with projective measures of annihilation anxiety (Hurvich, Benveniste, Howard, & Coonerty, 1993), try to measure the psychoanalytic concept of personal identity-related annihilation anxiety. They are many measures of existential anxiety (EA) with most of them is focused on fear of death (e.g.…”
Section: Measuring Eaamentioning
confidence: 99%